The opportunity structure, group characteristics, and strategy of ketok magic repair shops in Manado - Antonius Purwanto (Faculty of Social and Political Science, Universitas Airlangga, 2021)
The increase in internal migration has led to the emergence of ethnic minority migrant groups who work as entrepreneurs in various migration destinations in Indonesia. The migration that occurred in Manado shows that ethnic groups from certain regions form a unique group in the social network of repair shop owners and workers. This study aimed to describe the emergence and development of a ketok magic repair shop business in Manado which is owned by migrants from Blitar City, East Java. This study used a qualitative research method. Primary data were obtained from interviews and observations, while secondary data were obtained from literature studies. The results show that the opportunity structure in the form of requests for car repair and painting services as well as the ease of setting up a repair shop business has enabled the establishment of a number of ketok magic repair shops in Manado. Ethnic characteristics in the form of communities with high solidarity and strong social networks support repair shop activities well. This study concludes that community and social networks facilitate recruitment of workers and carry out repair shop promotion strategies because of high solidarity.